Poltergeist (2015) [videorecording (DVD)] - Spielberg, Steven, 1946-; Grais, Michael; Victor, Mark; Rockwell, Sam; DeWitt, Rosemarie; Harris, Jared, 1961-; Adams, Jane, 1965- (Twentieth Century Fox Home Entertainment, 2015)
The classic tale about a family whose suburban home is haunted by evil forces. When the terrifying apparitions escalate their attacks and hold the youngest daughter captive, the family must come together to rescue her before she disappears forever.